Pengelolaan Arsip Dinamis pada Dinas Perpustakaan dan Kearsipan Kota Palangka Raya - Irwani Irwani; Ika Ika (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to find out, 1) the management of dynamic records, 2) the factors that influence the management of documents, 3) the obstacles faced in archive management in the Library and Archives Office of the City of Palangka Raya. This study used qualitative research methods. The informants in this study were Administrative Section Staff, Dynamic Records Management Section Staff, and archivists at the Library and Archives Service Office of Palangka Raya City. Data is collected through observation, interviews, and documentation. The steps in analyzing data are data reduction, data presentation, and conclusion drawing. Checking the validity of the data is done by testing credibility with the strategy, including extending observations, research perseverance, triangulation, peer discussion, and member checking. The results of this study indicate that in general the management of dynamic records in the Library and Archives Office of the City of Palangka Raya includes: the creation of dynamic archives which include the creation of incoming letters and outgoing letters. Use of archives which include borrowing archives that use borrowed archive sheets and rediscovering archives that use a control card and archive search list. Obstacles in the management of records in the form of lack of filing rooms, lack of budgets in the procurement of archival facilities, and the lack of an archive staff